Assessment of Health-Related Quality of Life Among Patients Management Program of Chronic Diseases Type 2 Diabetes Mellitus - Fajriansyah1,2, Iskandarsyah A3, IM Puspitasari1,4, Keri Lestari1,4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Type 2 Diabetes Mellitus (T2DM) has significant adverse effects on health-related quality of life. PROLANIS program is a system of governance of health services and health education for social health insurance participants who suffer from type 2 diabetes mellitus to achieve the optimal quality of life independently. This research aims to measure quality of life in T2DM patient. The research was an analytical non-experimental study according to the patient’s perspective using prospective data collection techniques. The subjects are PROLANIS patient T2DM who comply inclusion and exclusion criteria.The data were collected by using the European Quality of Life 5 Dimensions 5 Levels (EQ-5D-5L) Indonesian questionnaire. Data analysis using EQ-5D preference weight for each health state using Indonesian EQ-5D-5L Value Set. Furthermore, the percentage of the patients’ problems, EQ-5D index (utility) and EQ-5D VAS were calculated. A total of 220 patients were included. Seventy-two different EQ-5D index values were described by the patients. Obtained 37 subjects (16.82%) had no problems. The EQ-5D index value highest is 1,000 (n = 32, 14,54%) and EQ-5D index value lowest is -0,384 (n = 1, 0,45%). EQ-5D index value has an average is 0.57 (SD 0,32) and EQ VAS value has an average is 72.19 (SD 14.73). This study also confirmed that T2DM remains a critical predictor of health outcomes among patients. Results from this study could be constructive in clinical practice, particularly in the early treatment of T2DM patients where improving HRQoL is still possible.